2016
DOI: 10.1007/s11655-016-2102-4
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermal imaging-based research on the intermediate structures of the lung and large intestine exterior-interior relationship in asthma patients

Abstract: This study is an initial step to validate the objective existence of Lung and Large Intestine exterior-interior relationship intermediate structures, as described in the Chinese classical medical literatures, through the functional imaging angle. The intermediate structures are the pathological reaction areas of the bronchial asthmatic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Some studies showed that in patients with PD and healthy subjects have an asymmetry in skin temperature at some acupoints, and this asymmetry has some significance in the early detection of the disease, early complementary diagnosis, and evaluation of the efficacy of complementary therapies. 32 Some acupoints show certain thermal characteristics of the skin, presenting an imbalance in skin temperature in the left and right specific acupoints in pathological processes such as chronic bronchial asthma, 33 chronic hepatitis, 34 breast hyperplasia, 35–37 infertility, 38 intracranial hypertension, 39 obesity, 40 and PD. 22 , 41 The imbalance in body surface temperature also has diagnostic value for a variety of pathological statuses, such as breast disease, 42 diabetic foot, 43 acute stroke, 44 and facial palsy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that in patients with PD and healthy subjects have an asymmetry in skin temperature at some acupoints, and this asymmetry has some significance in the early detection of the disease, early complementary diagnosis, and evaluation of the efficacy of complementary therapies. 32 Some acupoints show certain thermal characteristics of the skin, presenting an imbalance in skin temperature in the left and right specific acupoints in pathological processes such as chronic bronchial asthma, 33 chronic hepatitis, 34 breast hyperplasia, 35–37 infertility, 38 intracranial hypertension, 39 obesity, 40 and PD. 22 , 41 The imbalance in body surface temperature also has diagnostic value for a variety of pathological statuses, such as breast disease, 42 diabetic foot, 43 acute stroke, 44 and facial palsy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated that the circulation path of meridians seems to be characterized by better thermal conductivity [ 20 , 21 ]. Meridians can be sensitized by moxibustion on local acupoints, during which microcirculation becomes more exuberant, oxygen partial pressure of the deep tissue rises, and energy metabolism turns more vigorous along the circulation route of meridians [ 22 ]. This may explain that why the temperature of the distal acupoint of the stimulated meridian, which was far away from the local moxibustion acupoint, could rise significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with common clinical trials that intend to evaluate the effectiveness of a specific therapy, there is no consensus on the standardization of sample size estimation for such studies. Thus, the sample size estimation was mainly according to similar trials ( Hsiu et al, 2007 ; Raith et al, 2013 ; Fu et al, 2016 ) and actual research conditions of our study during different study phases. Finally, the total sample size was 80, with 40 subjects in the COPD group and 40 subjects in the healthy control group.…”
Section: Methodsmentioning
confidence: 99%